Anthracnose in Noni (Morinda citrifolia L.) in the State of Goiás (Research, Society and Development, 2021)
Noni (Morinda citrifolia L.) is a plant native to Southeast Asia that produces fruits with important nutritional and therapeutic properties. Therefore, in recent years, cultivation has expanded throughout Brazil. However, with the increase in the cultivated area, the occurrence of phytopathologies has become more frequent, which can compromise the productivity of the crop. Therefore, the objective was to report the occurrence of anthracnose in noni plants in the State of Goiás. Isolations were performed from leaf lesions of symptomatic plants collected in the municipalities of Ceres and Goianésia. The pathogenicity test of the isolates was performed. For the morphological characterization of the pathogen, slides were made and the structures were observed under light microscopy. The initial symptoms in the inoculated leaves were small circular spots of light brown color, circular and irregular, which gradually increased, becoming dark and with orange punctuations. The fungal colonies showed rapid growth and intense sporulation, grayish color with white margins. Hyaline mycelium septate and branched. Simple, elongated conidiophores. Hyaline, single-celled, straight, cylindrical or elliptical conidia. Based on the morphological characteristics, it can be concluded that the fungus of the genus Colletotrichum is the causative agent of anthracnose in noni in the State of Goiás.